Pengembangan Produk Celana Denim Berbasis Preferensi Konsumen Untuk Meningkatkan Keunggulan Bersaing - Fitriya Nur Azizah; Yati Rohayati; Meldi Rendra (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2024)
Research aim : This research aims to explore consumer preferences which will be used as a basis for product development in Micro, Small, and Medium Enterprises (MSMEs) that have received limited market response. Design/Methode/Approach : This research uses a survey research model with conjoint analysis method. Research Finding : The research findings indicate that developing products in Micro, Small, and Medium Enterprises (MSMEs) based on consumer preferences can enhance competitive advantage. Theoretical contribution/Originality : This research also proves that developing products in Micro, Small, and Medium Enterprises (MSMEs) based on consumer preferences through market surveys can effectively identify market needs. Practitionel/Policy implication : Developing products in Micro, Small, and Medium Enterprises (MSMEs) based on consumer preferences plays a role in increasing sales, enhancing product value, and improving competitiveness. Research limitation : In an effort to enhance the competitive advantage of Micro, Small, and Medium Enterprises (MSMEs), this research only focuses on the development of their products.